Social Workers' Attitudes towards Evidence-based Practice: A Multidimensional Perspective. - Kagan, Maya (British Journal of Social Work, 2022)
The current study presents a multidimensional model that integrates social workers' demographics, organisational context variables, evidence-based practice (EBP)-related factors and mental health variables and explores their contribution to social workers' attitudes to implementing EBP. This model aims to fill a gap in the limited empirical knowledge regarding the relative and joint contribution of these factors to explaining social workers' attitudes towards EBP, with an emphasis on mental health-related factors not sufficiently explored in this context to date. Structured questionnaires were administered to a sample of 560 Israeli social workers. The research findings revealed that length of professional experience, role ambiguity, work overload and burnout were negatively associated with attitudes to EBP. In contrast, possession of professional skills required for EBP implementation, workplace social support, organisational encouragement to implement EBP, exposure to colleagues' implementation of EBP and subjective well-being were positively associated with social workers' attitudes to EBP. No association was found between self-reported familiarity with EBP principles and attitudes to EBP. Improving social workers' organisational climate, remediating necessary EBP-related skills and encouraging the implementation and modelling of EBP at work, as well as addressing social workers' mental health issues, may significantly improve their attitudes towards implementing EBP in their professional practice.